Gest pośmiertnego pisania i inne „gesta” poetyckie (Verlaine, Rimbaud) - Kuczyńska-Koschany, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-GB; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-GB">The essay undertakes to investigate the phenomenon of erotic friendship as an “intertextual friendship” and, at the same time, “somatic (mis) understanding” (German: Un-beziehung). The following considerations include a discussion on the relationship between Paul Verlaine and Arthur Rimbaud, viewed first of all as bohemian characters of bohemian life and the protagonists of the mitologised homo-erotic relationship. Beside a hermeneutic attempt at describing the intimacy shared by both poets, or stages in the development of their intimate relations (with reference to French literature of the subject and texts that have not yet been translated into Polish), the author writes extensively on the reception of the relationship of the legendary pair of friends-lovers<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 9.5pt; mso-ansi-language: EN-US; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-US"> A<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-GB; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-GB">-war period, Agnieszka Holland’s film Total eclipse and the most recent poetical texts by Ewa Sonnenberg. The essay is complemented by some considerations on similar cases, analogous to the instance of the relationship between the two French poets: epistolary romance between R.M. Rilke and M. Tsvetaeva and, important within the context of the reception of Rimbaud in Poland — love/friendship exhibited in the letters between Andrzej Czajkowski and Anita Janowska.